Rapid Communication: Maternal melatonin implants improve fetal oxygen supply and body weight at term in sheep pregnancies. (19th November 2018) - Sales, Francisco; Peralta, Oscar A; Narbona, Eileen; McCoard, Sue; González-Bulnes, Antonio; Parraguez, Victor H
Abstract: Fetal hypoxia, resulting in oxidative stress in pregnancies, contributes to reduced fetal growth. Melatonin, a potent antioxidant, has been associated with improved oxidative status. Maternal oral melatonin supplementation in sheep from day 50 of gestation ameliorates the consequences of fetal growth restriction in sheep. In rats, melatonin supplementation increases fetal weight via improved placental efficiency and reduction of oxidative stress. The objective of this study was to evaluate whether melatonin supplementation of single (S)- or twin-bearing (T) ewes using either 0 (0MEL), 1 (18-mg MEL), or 2 (36-mg MEL) slow release 18-mg melatonin implants (Regulin) from 100 to 140 d of pregnancy ( n = 8 per group) influenced fetal oxygen supply and fetal weight. Fetal umbilical vein blood samples were collected at P140 and partial pressure of oxygen (PO2 ) and hemoglobin saturation by oxygen (SatHb) measured. The placenta from each fetus was excised and placentomes individually weighed and typed (A–D). Pregnancy rank, sex of the fetus, number of implants, and their interaction on fetal weight, blood gases, and placentome weight were analyzed using ANOVA. A 22% and 14% increase ( P < 0.05) in body weight was obtained in 36- and 18-mg MEL compared with 0 MEL twin male fetuses, respectively, but no treatment effects were observed in singletons or females from twin pregnancies. Fetuses from ewes receiving 36-mg MEL had an 18% to 20% increase in cord PO2 ( P < 0.05) compared with 18-mg MEL and 0MEL fetuses, which in turn did not differ. Fetal weight was positively correlated with PO2 ( r = 0.37; P = 0.02), SatHb ( r = 0.26; P = 0.03), and O2 content ( r = 0.236; P = 0.048). No treatment effect on placentome average weight, total placentome weight per fetus or per ewe, nor total number of placentomes per fetus was observed. However, placentae from 36-mg MEL fetuses had a greater proportion of Type C ( P < 0.05) than 0MEL and 18-mg MEL ewes, and tended to have a lower proportion of Type A ( P = 0.1) and a greater proportion of Type D ( P = 0.06) placentomes, compared with 0MEL ewes. These results indicate that maternal melatonin implants, independently of sex, improve oxygen supply to the fetus, which could potentially improve lamb vigor at birth. In addition, melatonin can increase fetal weight of twin males, by improving placental adaptation and fetal blood oxygenation.